3ax-8a=b-18x
3ax+18x=b+8a
3x(a+6)=b+8a
3x=(b+8a)/(a+6)
x=(b+8a)/3(a+6)
3a*(b+8a)/3(a+6)=b-18*(b+8a)/3(a+6)
a(b+8a)/(a+6)=b-6(b+8a)/(a+6)
a(b+8a)=b(a+6)-6(b+8a)
ab+8a^2=ab+6b-6b-48a
ab+8a^2=ab-48a
8a^2=-48a
8a^2+48a=0
8a(a+6)=0 so a=0,-6
0=b-18x or -18x+48=b-18x
-b=-18x or 48=b
let b=18 if a =-6
I think it's one of the last 2 they equal the same thing, so -8+(-3) is the answer.
Answer:
(-3,-2)
(-3,4)
(3,4)
(3,-3)
Step-by-step explanation:
Answer:
(x,0)
Step-by-step explanation:
Answer:
he bought the t shirt for rs 1880